Strategies for deploying triple artemisinin-based combination therapy in the Greater Mekong Subregion - de Haan F. (2023)
Background: This is a qualitative study to identify implementation challenges for deploying triple artemisinin-based combination therapy (TACT) in the Greater Mekong Subregion (GMS) of Southeast Asia and to explore strategies to overcome these challenges. Methods: In-depth interviews were conducted in three countries that have repeatedly been confronted with ACT failures: Cambodia, Vietnam, and Lao PDR. Thirty-nine key stakeholders in the healthcare systems in these countries were interviewed. One participatory workshop was conducted in Cambodia, where scenarios for potential TACT deployment were discussed. Results: The results section is organized around four strategic themes that emerged from the data: policy support, data and evidence, logistics and operation, and downstream engagement. The study revealed that countries in the GMS currently rely on ACT to eliminate Plasmodium falciparum malaria by 2025. TACT is, however, considered to be a useful backup strategy in case of future treatment failures and to prevent the re-establishment of malaria. The study showed that a major challenge ahead is to engage decision makers and healthcare providers into deploying TACT, given the low case incidence of falciparum malaria in the GMS. Interview respondents were also skeptical whether healthcare providers would be willing to engage in new therapies for a disease they hardly encounter anymore. Hence, elaborate information dissemination strategies were considered appropriate and these strategies should especially target village malaria workers. Respondents proposed several regulatory and programmatic strategies to anticipate the formation of TACT markets in the GMS. These strategies include early dossier submission to streamline regulatory procedures, early stakeholder engagement strategies to shorten implementation timelines, and inclusion of TACT as second-line therapy to accelerate their introduction in case they are urgently needed. Conclusions: This paper presents a qualitative study to identify implementation challenges for deploying TACT in the GMS and to explore strategies to overcome these challenges. The findings could benefit researchers and decision makers in strategizing towards potential future deployment of TACT in the GMS to combat artemisinin and partner drug resistance.